1961
DOI: 10.1139/v61-187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ambient Oxygen on the Semiconductivities of Evaporated Films of Mesonaphthodianthrene and Mesonaphthodianthrone

Abstract: The electrical conductivity of an "evaporated" film of mesonaphthodianthrene increases when the film is exposed t o oxygen. The increase in conductivity is associated with changes in the semiconductivity activation energies. The activation energy for the oxygen-free anthrene (bulk conduction) is 0.74 ev while that associated with oxygen adsorption (surface conduction) is 0.40 ev. In marked contrast, the conductivity of an evaporated film of mesonaphthodianthrone decreases when exposed t o oxygen. An oxygen-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1961
1961
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It is widely believed that such p-type OSCs are unintentionally doped by oxygen from air. [1][2][3] The properties of organic electronic devices such as sensors, transistors, and light-emitting diodes are affected by oxygen gas. [4][5][6] In an oxygen doping process, an electron is transferred to an oxygen molecule, and a molecular cation and an oxygen anion are formed.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely believed that such p-type OSCs are unintentionally doped by oxygen from air. [1][2][3] The properties of organic electronic devices such as sensors, transistors, and light-emitting diodes are affected by oxygen gas. [4][5][6] In an oxygen doping process, an electron is transferred to an oxygen molecule, and a molecular cation and an oxygen anion are formed.…”
Section: Introductionmentioning
confidence: 99%
“…I n previous papers we have shown that the semiconductivities of films of mesonaphthodianthrene formed by sublimation are increased markedly by exposure to oxygen (4,5). I t was further shown that oxygen produces a new conduction mechanism with a lower activation energy, and we have attributed the effect to the formation of a complex between oxygen and the surface ~nolecules.…”
Section: Introductionmentioning
confidence: 82%
“…However, for explaining the observed sensitivity one should take into account not only the Fe 2 O 3 content but also the polymeric/carbonaceous matrix: (i) the particle coating maintains a good dispersion between the small grains (coatings prevents grain growth and agglomeration) thus avoiding sintering; (ii) the carbonaceous shell could act like a stabilizer for the oxide phase at higher temperatures; (iii) the appearance of nanometric-size channels, due to the loss of gas and shrinkage in volume could favor gas penetration onto the Fe 2 O 3 interface [40]; (iv) the probably low contribution of the carbonaceous component of the calcined composite to the semiconductivity of the thick film should not be neglected. In fact it is already known that, depending on the chemical process and on the heating temperature, amorphous carbon could present different degrees of semiconductivity [41].…”
Section: Preliminary Sensor Testsmentioning
confidence: 99%